A Glimpse into the Satellite DNA Library in Characidae Fish (Teleostei, Characiformes) - Utsunomia, Ricardo [UNESP]; Ruiz-Ruano, Francisco J.; Silva, Duilio M. Z. A. [UNESP]; Serrano, Erica A. [UNESP]; Rosa, Ivana F. [UNESP]; Scudeler, Patricia E. S. [UNESP]; Hashimoto, Diogo T. [UNESP]; Oliveira, Claudio [UNESP]; Camacho, Juan Pedro M.; Foresti, Fausto [UNESP] (Frontiers Media Sa, 2017)
Satellite DNA (satDNA) is an abundant fraction of repetitive DNA in eukaryotic genomes and plays an important role in genome organization and evolution. In general, satDNA sequences follow a concerted evolutionary pattern through the intragenomic homogenization of different repeat units. In addition, the satDNA library hypothesis predicts that related species share a series of satDNA variants descended from a common ancestor species, with differential amplification of different satDNA variants. The finding of a same satDNA family in species belonging to different genera within Characidae fish provided the opportunity to test both concerted evolution and library hypotheses. For this purpose, we analyzed here sequence variation and abundance of this satDNA family in ten species, by a combination of next generation sequencing (NGS), PCR and Sanger sequencing, and fluorescence in situ hybridization (FISH). We found extensive between-species variation for the number and size of pericentromeric FISH signals. At genomic level, the analysis of 1000s of DNA sequences obtained by Illumina sequencing and PCR amplification allowed defining 150 haplotypes which were linked in a common minimum spanning tree, where different patterns of concerted evolution were apparent. This also provided a glimpse into the satDNA library of this group of species. In consistency with the library hypothesis, different variants for this satDNA showed high differences in abundance between species, from highly abundant to simply relictual variants.
Keywords: concerted evolution; repetitive DNA; in situ hybridization; satellite DNA; genome evolution